P.187 Evaluating congruency between intramedullary and subdural pressure in a porcine model of acute spinal cord injury. (November 2021) - Rizzuto, MA; Allard Brown, A; Kim, K; So, K; Manouchehri, N; Webster, M; Fisk, S; Griesdale, DE; Sekhon, MS; Streijger, F; Kwon, BK
Abstract : Background: Clinical guidelines recommend MAP maintenance at 85-90 mmHg to optimize spinal cord perfusion post-SCI. Recently, there has been increased interest in spinal cord perfusion pressure as a surrogate marker for spinal cord blood flow. The study aims to determine the congruency of subdural and intramedullary spinal cord pressure measurements at the site of SCI, both rostral and caudal to the epicenter of injury. Methods: Seven Yucatan pigs underwent a T5 to L1 laminectomy with intramedullary (IM) and subdural (SD) pressure sensors placed 2 mm rostral and 2 mm caudal to the epicenter of SCI. A T10 contusion SCI was performed followed by an 8-hour period of monitoring. Axial ultrasound images were captured at the epicenter of injury pre-SCI, post-SCI, and hourly thereafter. Results: Pigs with pre-SCI cord to dural sac ratio (CDSR) of >0.8 exhibited greater occlusion of the subdural space post-SCI with a positive correlation between IM and SD pressure rostral to the injury and a negative correlation caudal to the epicenter. Pigs with pre-SCI CDSR <0.8 exhibited no correlation between IM and SD pressure. Conclusions: Congruency of IM and SD pressure is dependent on compartmentalization of the spinal cord occurring secondary to swelling that occludes the subdural space.